Vaccine development for leptospirosis: a systematic review - Surendran, Yocyny; Nandikha, Mahalingam; Amin-Nordin, Syafinaz; Dhanda, Sandeep Kumar; Mohd Ali, Mohamad Ridhuan; Joseph, Narcisse Ms (Medknow Publications, 2023)
Objective: To assess the efficacy of various types of vaccines developed for leptospirosis. Methods: A comprehensive search was conducted in three databases: PubMed, Scopus, and Cochrane Library. Two authors (YS and MN) selected the articles based on manual screening. The study eligibility criteria are all Leptospira species regardless of any cluster (pathogenic, intermediate and non-pathogenic). This study recorded articles with positive and negative results and showed a comparison among various membrane proteins as vaccine candidates. The studies on the effectiveness of outer membrane protein as vaccine candidates were also included. The articles obtained in the databases were imported into the WPS spreadsheet, and duplicate documents were removed manually. Results: A total of 24 studies were included in the review, which evaluated various types of leptospirosis vaccines. Multiple vaccines were developed and tested; however, the heterogeneity of Leptospira species pose a challenge. As an effective approach, an epitope based vaccine shows quite a promising result. However, sufficient validation, testing and clinical trials are required. Conclusions: Developing an effective vaccine for leptospirosis remains a global health priority. While significant progress has been made in recent years, there is a need for further research to optimize vaccine development and to ensure that vaccines are accessible and effective for high-risk populations.